A study on the solid waste composition and solid waste generation rate in commercial area of Taman Sri Gading, Kuantan - Norafitah, Mahidin (2013)
Nowadays, rapid development and increase in population had contributed to a variety of problems including the uncontrolled environmental problems. As a result the unused resources will be classified as waste. One of the sources of waste generated is from the commercial area. This study will be conducted in Taman Sri Gading, Kuantan, Pahang. This study is aimed at determining the commercial solid waste composition, waste generation rate and the factors that influence the solid waste generation rate. There are two types of premises involved in this study which are product and service type premises. In order to get the generation rate, this study is carried out to get the data of waste collection by segregation and weighing of the solid waste from 30 premises which have been selected randomly. The solid waste collected from the samples will be segregate into six components which are organic, food scraps, paper & cardboard, plastic, glasses, aluminum and others. Other than that, there is about 30 questionnaires are distributed to get some information about the type of waste generated, solid waste management and public awareness. The questionnaire distribution is a way to identify and collect the information on factors effecting the solid waste composition. At the end of data collection, all of the data will be analyzed and fmdings from the analysis are being evaluated, discussed and summarized. According to this study, product type premise produced about 3.15 kg/employee.day and service type premises produced about 3.23 kg/employee.day. The range of waste composition for food waste in product and service type premises were about 1.45 to 8.35 kg/day and 0,00 to 3.88 kg/day. For paper and cardboard, the waste compositions produced by product and service type premises were about 0.02 to 0.7 kg/day and 0.03 to 0,98 kg/day. Besides that, the waste compositions on plastics for product and service type premises were 0.06 to 0.66 kg/day and 0.00 to 0.57 kg/day. Meanwhile, the composition of glass waste for both product and service type premises were 0.00 to 0.65 kg/day and 0.00 to 0.04 kg/day. For aluminium waste composition, it was about 0.00 to 0.07 kg/day for product type premises and 0.00 to 0.03 kg/day for service .type premises. The composition for the others wastes such as rubber for product and service type premises were about 0.00 to 0.44 kg/day and 0.07 to 1.14 kg/day. The higher waste composition in this area was food waste and the 1o'yest waste composition was aluminium. It was because of the factors of Asian people which had habit on eating. The other factors that influenced the solid waste generated because of that area was an urban area that was developed. So, the population growth had influenced the solid waste generation rate in Taman Sri Gading.